Three distinct modes of intron dynamics in the evolution of eukaryotes - Carmel, Liran; Wolf, Yuri I.; Rogozin, Igor B.; Koonin, Eugene V. (Genome Research, 2007)
Several contrasting scenarios have been proposed for the origin and evolution of spliceosomal introns, a hallmark of eukaryotic genes. A comprehensive probabilistic model to obtain a definitive reconstruction of intron evolution was developed and applied to 391 sets of conserved genes from 19 eukaryotic species. It is inferred that a relatively high intron density was reached early, i.e., the last common ancestor of eukaryotes contained >2.15 introns/kilobase, and the last common ancestor of multicellular life forms harbored ∼3.4 introns/kilobase, a greater intron density than in most of the extant fungi and in some animals. The rates of intron gain and intron loss appear to have been dropping during the last ∼1.3 billion years, with the decline in the gain rate being much steeper. Eukaryotic lineages exhibit three distinct modes of evolution of the intron–exon structure. The primary, balanced mode, apparently, operates in all lineages. In this mode, intron gain and loss are strongly and positively correlated, in contrast to previous reports on inverse correlation between these processes. The second mode involves an elevated rate of intron loss and is prevalent in several lineages, such as fungi and insects. The third mode, characterized by elevated rate of intron gain, is seen only in deep branches of the tree, indicating that bursts of intron invasion occurred at key points in eukaryotic evolution, such as the origin of animals. Intron dynamics could depend on multiple mechanisms, and in the balanced mode, gain and loss of introns might share common mechanistic features.